Adsorption of picloram herbicide on iron oxide pillared montmorillonite - Marco Brown, José Luis (2012)
The adsorption of picloram on Fe Oxide Pillared Clays (PILC) as a possible basis for the development of adsorbent materials for the remediation of polluted environments was studied. To this end, after characterizing PILC obtained from raw clay from Wyoming, USA by XRD, elemental analysis, Mössbauer spectroscopy, DTA, TGA and N2 adsorption (BET), the picloram adsorption was studied at constant pH and ionic strength after 48 h equilibration with an aqueous solution of PCM. PCM adsorbed samples were characterized by SEM, zeta-potential vs pH functions, FTIR and TGA-DTA and the adsorption was modellated using Langmuir and Freundlich models. The results reveal that the surface area and interlayer space of PILC are bigger than those of raw montmorillonite. An analysis of the adsorption isotherms of picloram on the PILC showed that picloram adsorption increases with decreasing pH. The adsorption of PCM on PILC was 150 times higher than that found for raw montmorillonite under similar conditions. The zeta-potential vs pH functions shape and FTIR indicated that PCM coordinates the surface iron centers throughout pyridinic nitrogen atom forming inner-sphere complexes. The much greater PCM adsorption on PILC turns the process into an excellent candidate to be used for dosing or remediation of pesticides.